Influenza Vaccine Does Not Increase the Risk of Coronavirus or Other Noninfluenza Respiratory Viruses: Retrospective Analysis From Canada, 2010–2011 to 2016–2017. (22nd May 2020) - Skowronski, Danuta M; Zou, Macy; Clarke, Quinten; Chambers, Catharine; Dickinson, James A; Sabaiduc, Suzana; Olsha, Romy; Gubbay, Jonathan B; Drews, Steven J; Charest, Hugues; Winter, Anne-Luise; Jassem, Agatha; et al.
Abstract: Influenza vaccine effectiveness against influenza and noninfluenza respiratory viruses (NIRVs) was assessed by test-negative design using historic datasets of the community-based Canadian Sentinel Practitioner Surveillance Network, spanning 2010–2011 to 2016–2017. Vaccine significantly reduced the risk of influenza illness by >40% with no effect on coronaviruses or other NIRV risk.